ANALISIS PEMIKIRAN ALI YAFIE DAN SAHAL MAHFUZD DALAM FIQIH SOSIAL TERHADAP PERKEMBANGAN HUKUM ISLAM - Jumain Azizi; Opan Satria Mandala (JURNAL MAHASANTRI, 2022)
This study aims to: determine the concept of social fiqh thought KH. Ali Yafie and KH. Sahal Mahfuzd and knowing and analyzing the differences and similarities of the concepts of social fiqh KH Ali Yafie and KH Sahal Mahfuz and how the implications for the development of Islamic law, this type of research is a conceptual comparison, the results of this study show that Ali Yafie in initiating social fiqh begins with a discussion of Al -The Qur'an then penetrates into actual social and legal issues. As a faqih, Ali Yafie wants a complete understanding of the Qur'an in the face of today's increasingly layered challenges. Ali Yafie proposed five main themes in order to fully understand the Qur'an, namely: first, affirmation and strengthening of the existence of revelation; secondly the recognition of the problem of divinity; the third view of Islam; fourth, the introduction of humans and humanity; and fifth, views on life problems. Meanwhile, Kiai Sahal's style of fiqh thought, apart from being able to be seen in terms of the methodology of finding and developing the law used, can also be seen in terms of its responsiveness to both social and political responses.